A pharmacokinetic comparison of two voriconazole formulations and the effect of CYP2C19 polymorphism on their pharmacokinetic profiles - Chung H; Lee H; Han H; An H; Lim KS; Lee YJ; Cho JY; Yoon SH; Jang IJ; Yu KS (Dove Medical Press, 2015)
Hyewon Chung,1,* Howard Lee,1,2,* HyeKyung Han,1 Hyungmi An,1 Kyoung Soo Lim,1,3 YongJin Lee,4 Joo-Youn Cho,1 Seo Hyun Yoon,1 In-Jin Jang,1 Kyung-Sang Yu1 1Department of Clinical Pharmacology and Therapeutics, Seoul National University College of Medicine, Seoul National University Hospital, Seoul, Republic of Korea; 2Department of Transdisciplinary Studies, Graduate School of Convergence Science and Technology, Seoul National University, Seoul, Republic of Korea; 3Department of Clinical Pharmacology and Therapeutics, CHA University School of Medicine and CHA Bundang Medical Center, Seongnam, Republic of Korea; 4Medical and Regulatory Affairs Team, Samyang Biopharmaceuticals Corporation, Seoul, Republic of Korea *These authors contributed equally to this work Purpose: SYP-1018 is a lyophilized polymeric nanoparticle formulation of voriconazole that is under development for intravenous dosing. This study compared the pharmacokinetic and tolerability profiles of SYP-1018 with those of Vfend®, the marketed formulation of voriconazole. The effect of CYP2C19 polymorphism on the voriconazole pharmacokinetics was also evaluated.  Methods: An open-label, two-treatment, two-period, two-sequence crossover study was conducted in 52 healthy male volunteers, who randomly received a single intravenous infusion of either of the two voriconazole formulations at 200 mg. Blood samples were collected up to 24 hours after drug administration for pharmacokinetic analysis. The plasma concentrations of voriconazole were determined using liquid chromatography with tandem mass spectrometry, and the pharmacokinetic parameters were estimated using a noncompartmental method. CYP2C19 genotype was identified in 51 subjects.  Results: The geometric mean ratio (90% confidence interval) of SYP-1018 to Vfend® was 0.99 (0.93–1.04) for the maximum plasma concentrations (Cmax) and 0.97 (0.92–1.01) for the area under the concentration–time curve (AUC) from dosing to the last quantifiable concentration (AUClast). Nineteen homozygous extensive metabolizers (EMs, *1/*1), 19 intermediate metabolizers (IMs, *1/*2 or *1/*3), and ten poor metabolizers (PMs, *2/*2, *2/*3, or *3/*3) were identified, and the pharmacokinetic comparability between SYP-1018 and Vfend® was also noted when analyzed separately by genotype. The systemic exposure to voriconazole was greatest in the PM group, followed by the IM, and then the EM groups. Furthermore, the intrasubject variability for Cmax and AUClast was greater in IMs and PMs than in EMs. No serious adverse event occurred, and both treatments were well tolerated.  Conclusion: SYP-1018 had comparable pharmacokinetic and tolerability profiles to Vfend® after a single intravenous infusion. CYP2C19 genotype affected not only the pharmacokinetics of voriconazole, but its intrasubject variability. SYP-1018 can be further developed as a clinically effective alternative to Vfend®. Keywords: voriconazole, pharmacokinetics, pharmacogenetics, CYP2C19